Pengaruh Emotion Focused Coping dan Self love Terhadap Pencegahan Self Harm Behaviour Pada Mahasiswa Keperawatan STIKes Flora - Haflah, Nurul; Sari, Youlanda; Rahmadani, Rina (JINTAN: Jurnal Ilmu Keperawatan, 2025)
Mental health problems are a challenge for global development and are a hot issue in Indonesia. One of the mental health phenomena that students often experience is self-harm as a maladaptive coping mechanism when experiencing stressors, emotional stress, feeling sad or physically ill, facing problems or situations that lead to distress and the inability to control emotions. Self-love is important for having good mental health because it is an important component in self-esteem and health, as well as building resilience when someone experiences problems. The aim of the research is to determine the influence of Emotion Focused Coping and Self-love on the Prevention of Self-Harm Behavior in nursing students. Correlation and regression research design with Proportional Random Sampling technique. The population in this study were 126 STIKes Flora nursing students. Data were analyzed using linear regression statistical tests. From the research results, it is known that there is an influence of Emotion Focused Coping and Self Love on the Prevention of Self-Harm Behavior in nursing students with a P value of emotion focused coping of 0.001 and self-love of 0.008, with a negative direction, the higher the emotion focused coping and self-love, the lower the self-harm behavior will be. The results of this research are expected for students to be able to apply good coping in facing problems and have good self-love in dealing with the stressors they face